Implementation of smart room system based PLC and block diagram function programming - Triwijaya, Santi; Prasetyo, Yuli; Triyono, Budi; Nur Prakoso, Dimas; Multazam, Teuku (Journal Geuthee of Engineering and Energy, 2024)
Technological developments have brought a revolution in the smart home concept, with smart rooms becoming the main focus to increase comfort, efficiency and security. This article explores the concept of a Programmable Logic Controller (PLC) based smart room with Function Block Diagram (FBD) programming. PLCs, which were originally used in industry, were introduced into the smart home environment as a central brain capable of managing and controlling electronic devices. FBD programming, with its visual approach, provides an intuitive programming solution by using function blocks to represent control logic. Through the use of FBD-based PLCs, smart rooms can be effectively automated, including lighting, temperature and security aspects. The advantages of this method include an easy-to-understand programming interface and the ability to design control logic without requiring a deep understanding of programming languages. The research results show that FBD-based PLCs provide an efficient and effective solution to improve the function of smart rooms. This implementation can provide significant benefits in terms of energy management, occupant comfort and home security. Thus, the PLC-based smart room concept with FBD programming marks a step forward in realizing a smart home that is responsive, connected, and can be adapted to the needs of residents.